2015
DOI: 10.1021/nl503961p
|View full text |Cite
|
Sign up to set email alerts
|

Light-Controlled Spin Filtering in Bacteriorhodopsin

Abstract: The role of the electron spin in chemistry and biology has received much attention recently owing to to the possible electromagnetic field effects on living organisms and the prospect of using molecules in the emerging field of spintronics. Recently the chiral-induced spin selectivity effect was observed by electron transmission through organic molecules. In the present study, we demonstrated the ability to control the spin filtering of electrons by light transmitted through purple membranes containing bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 25 publications
1
60
0
Order By: Relevance
“…49 Note that both for the wild bR and the mutant, the preferred spin direction (higher faradaic current) was observed when the modified nickel was magnetized in the “UP” direction.…”
Section: Light Controlled Spin Filtering Across the Bacteriorhodopsinmentioning
confidence: 97%
“…49 Note that both for the wild bR and the mutant, the preferred spin direction (higher faradaic current) was observed when the modified nickel was magnetized in the “UP” direction.…”
Section: Light Controlled Spin Filtering Across the Bacteriorhodopsinmentioning
confidence: 97%
“…This system has been previously suggested as a candidate for bio‐electronics, and in a former study, wild‐type bR was shown to have spin‐filtering properties . Spin‐dependent electrochemical studies were conducted on purple membrane containing a mutant of bacteriorhodopsin (bR) adsorbed on nickel substrates . The bR protein is embedded in its native membrane environment, resembling most closely its natural structure.…”
Section: The Ciss Effectmentioning
confidence: 99%
“…There are plenty of materials to be conjugated with bR. As an example, according to the reports on light-controlled spin filtering in bR [89], magnetic nanoparticles such as nickel and iron oxide can be an area of interest for further research.…”
Section: Summary and Perspectivesmentioning
confidence: 99%